The significance of rota representation in the design of rotas - Gärtner, J.; Wahl, S. (Scandinavian Journal of Work, Environment & Health, 1998)
Shift scheduling is based on some representation of shift schedules. The number of different representations currently used is high, and one might expect small practical differences between these representations. However, an analysis of several prominent representations revealed strong differences regarding possible outcomes of the scheduling process and the effort needed for their assessment. Limitations of some representations do not only concern specific rota design issues, such as different staffing levels or different workhours, but also rather simple and straightforward rotas. Furthermore, there is no single representation that is strictly and unequivocally better than the others. Most representations simplify the development of some rotas, while they make it very difficult or even impossible to develop others. Therefore, both designers and the computer systems used for design should use and support several representations and therefore allow smooth transitions between them. In addition knowledge about rota construction techniques applied, should be maintained, as it may ease assessment dramatically.
Keywords: assessment of shift rotas; complexity analysis; computer-supported shift scheduling; shift scheduling